Spanish Trinidad - Morales Padrón, Francisco; García De la Torre, Armando (Ian Randle Publishers, 2012)
History of Trinidad's 300 under Spanish rule, written from the Spanish perspective. Examines the policies that fuelled Trinidad's economic and demographic transformation from a remote outpost to a prized possession of Spain, ultimately seized by the British.